Revision of the genus Phyllotrella Gorochov, 1988 (Orthoptera: Gryllidae: Podoscirtinae: Podoscirtini) - Wei, Shu-Fei; Wang, Dan; Zhang, Tao; He, Zhu-Qing (Zootaxa, 2023)
The genus Phyllotrella Gorochov, 1988 presently comprises four described species, P. planidorsalis Gorochov, 1988, P. fumingi Sun & Liu, 2019, P. hainanensis Sun & Liu, 2019 and P. transversa Sun & Liu, 2019. In this study, the results of this genus are based on molecular and morphological features. The molecular result shows that the genetic distance among these individuals from different areas was 0.767%–1.386%. Thus, we consider them as same species. However, based on the similarities and differences of their male genitalia, we suggest treat these species as two subspecies P. planidorsalis planidorsalis (= P. hainanensis syn. nov. and P. transversa syn. nov.) and P. planidorsalis fumingi stat. nov.